HSP90AA1 interacts with CSFV NS5A protein and regulates CSFV replication via the JAK/STAT and NF-κB signaling pathway - Liu, Chenchen; Zhao, Wei; Su, Jia; Chen, Xiaochun; Zhao, Feifan; Fan, Jindai; Li, Xiaowen; Liu, Xiaodi; Zou, Linke; Zhang, Mengru; Zhang, Zilin; Zhang, Liangliang; et al. (Frontiers in Immunology, 2022)
Classical swine fever (CSF), caused by the classical swine fever virus (CSFV), is a highly contagious and fatal viral disease, posing a significant threat to the swine industry. Heat shock protein 90 kDa alpha class A member 1 (HSP90AA1) is a very conservative chaperone protein that plays an important role in signal transduction and viral proliferation. However, the role of HSP90AA1 in CSFV infection is unknown. In this study, we found that expression of HSP90AA1 could be affected in PK-15 and 3D4/2 cells infected by CSFV. Over-expression of HSP90AA1 could inhibit CSFV replication and functional silencing of HSP90AA1 gene promotes CSFV replication. Further exploration revealed that HSP90AA1 interacted with CSFV NS5A protein and reduced the protein levels of NS5A. Since NS5A has an important role in CSFV replication and is closely related to the type I IFN and NF-κB response, we further analyzed whether HSP90AA1 affects CSFV replication by regulating type I IFN and NF-κB pathway responses. Our research found HSP90AA1 positively regulated type I IFN response by promoting STAT1 phosphorylation and nuclear translocation processes and promoted the nuclear translocation processes of p-P65. However, CSFV infection antagonizes the activation of HSP90AA1 on JAK/STAT and NF-κB pathway. In conclusion, our study found that HSP90AA1 overexpression significantly inhibited CSFV replication and may inhibit CSFV replication by interacting with NS5A and activating IFN-I and NF-κB signaling pathways. These results provide new insights into the mechanism of action of HSP90AA1 in CSFV infection, which abundant the candidate library of anti-CSFV.